Rumen-protected methionine supplementation alters lipid profile of preimplantation embryo and endometrial tissue of Holstein cows - Stella, Stephanie L.; Guadagnin, Anne R.; Velasco-Acosta, Diego A.; Ferreira, Christina R.; Rubessa, Marcello; Wheeler, Matthew B.; Luchini, Daniel; Cardoso, Felipe C. (Frontiers in Veterinary Science, 2024)
Our objective is to evaluate the effects of feeding rumen-protected Met (RPM) throughout the transition period and early lactation on the lipid profile of the preimplantation embryos and the endometrial tissue of Holstein cows. Treatments consisted of feeding a total mixed ration with top-dressed RPM (Smartamine® M, Adisseo, Alpharetta, GA, USA; MET; n = 11; RPM at a rate of 0.08% of DM: Lys:Met = 2.8:1) or not (CON; n = 9, Lys:Met = 3.5:1). Endometrial biopsies were performed at 15, 30, and 73 days in milk (DIM). Prior to the endometrial biopsy at 73 DIM, preimplantation embryos were harvested via flushing. Endometrial lipid profiles were analyzed using multiple reaction monitoring-profiling and lipid profiles of embryos were acquired using matrix assisted laser desorption/ionization mass spectrometry. Relative intensities levels were used for principal component analysis. Embryos from cows in MET had greater concentration of polyunsaturated lipids than embryos from cows in CON. The endometrial tissue samples from cows in MET had lesser concentrations of unsaturated and monounsaturated lipids at 15 DIM, and greater concentration of saturated, unsaturated (specifically diacylglycerol), and monounsaturated (primarily ceramides) lipids at 30 DIM than the endometrial tissue samples from cows in CON. In conclusion, feeding RPM during the transition period and early lactation altered specific lipid classes and lipid unsaturation level of preimplantation embryos and endometrial tissue.